Flexible Pressure Sensors Based on Bionic Microstructures: From Plants to Animals. Issue 5 (12th January 2022) - Tan, Yuewu; Liu, Xuehong; Tang, Wei; Chen, Jing; Zhu, Zhengfang; Li, Lin; Zhou, Nian; Kang, Xiaoyang; Xu, Dongliang; Wang, Lei; Wang, Guixue; Tan, Hui; et al.
Abstract: Numerous wearable devices have been applied in people's daily lives. As the core component of wearable devices, flexible pressure sensors play an especially important role in various fields because of their excellent adaptability to the environment. Various high‐performance flexible pressure sensors have been developed, and much research is still being conducted to increase the performance of flexible pressure sensors. A variety of materials with excellent properties have been created, many advanced manufacturing methods have been developed, and different microstructures have been attempted and applied to flexible pressure sensors. To optimize the performance of sensors, flexible pressure sensors with bionic microstructures from the perspective of bionics have attracted increasing attention, which can bring new designs and improve the performance. This paper mainly summarizes various kinds of flexible pressure sensors with bionic structures developed in recent years. The main contents include the following parts: an introduction to the current state‐of‐the‐art flexible pressure sensors; substrate and active materials, sensing mechanisms, key parameters, and sensitivity optimization strategies; various kinds of bionic microstructures applied to flexible pressure sensors and characterization of the performance; applications of flexible pressure sensors; and prospects and potential challenges of flexible pressure sensors. Abstract : To optimize the performance of sensors, flexible pressure sensors with bionic microstructures from the perspective of bionics have attracted increasing attention, which can bring new designs and improve the performance. This paper mainly summarizes various kinds of flexible pressure sensors with bionic structures developed in recent years.